Elevated Preoperative Serum Bilirubin Improves Reperfusion Injury and Survival Postliver Transplantation. Issue 8 (August 2017) - Spetzler, Vinzent; Goldaracena, Nicolas; Kaths, Johann Moritz; Marquez, Max; Selzner, Markus; Selzner, Nazia
Abstract : Background: The cytoprotective effects of hemeoxygenase-1 and its product biliverdin/bilirubin are widely acknowledged in experimental transplant medicine. However, its potentially beneficial effect during organ reperfusion is not established. Methods: In a matched study, we compared markers of reperfusion injury (alanine aminotransferase/aspartate aminotransferase) and transplantation outcome (complication rates, liver function, and survival) between recipient groups with "normal" versus "increased" preoperative bilirubin values. Groups were matched for donor and recipient age, liver disease, year of transplantation, and recipient's preoperative condition (modified model for end-stage liver disease score excluding bilirubin). Results: The postoperative transaminase peak was significantly higher when comparing the "normal" to the "increased" bilirubin group (maximum aspartate aminotransferase "normal" 2013 [325-13 210] U/L vs "increased" 1360 [221-15 460] U/L, P = 0.006; maximum alanine aminotransferase "normal" 1151 [82-6595] U/L vs "increased" 820 [66-5382] U/L, P = 0.01). Grafts in the "increased" bilirubin group had faster recovery of graft function with faster decrease in international normalized ratio at days 3 and 7 posttransplantation in the "increased" vs "normal" bilirubin group. Although long-term functional parameters (international normalized ratio and bilirubin posttransplantation) as well as surgical and biliary complication rates were similar in both groups, 1-year survival rates were significantly higher in the group with increased preoperative bilirubin (graft survival, "normal" 86% vs "increased" 97%; P = 0.006). Conclusions: Increased bilirubin levels of liver graft recipients before transplantation are associated with reduced reperfusion injury and improved survival after transplantation.